Flame-retardant pc / abs composition, method for preparing the same, and use thereof

CN119931303BActive Publication Date: 2026-10-30KINGFA SCI & TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510182432.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2026-10-30
Estimated Expiration
2045-02-19

AI Technical Summary

Technical Problem

[0005]本发明的目的在于克服现有技术中阻燃PC/ABS材料中线性膨胀系数及各向异性较大及刚性不足的缺陷,本发明将提供一种阻燃PC/ABS组合物及其制备方法和应用

Benefits of technology

[0033]相对于现有技术,本发明具有以下有益效果:本发明通过将300-600目云母粉A和20-40目云母粉B复配,两种云母粉可以取长补短,在保持良好的阻燃性能的基础上,使得组合物的刚性可以有效提高,线性膨胀系数及其各向异性可以有效降低,综合实现高刚性以及尺寸稳定性的阻燃PC/ABS组合物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005277514850000071
    Figure BDA0005277514850000071
  • Figure BDA0005277514850000072
    Figure BDA0005277514850000072
  • Figure BDA0005277514850000081
    Figure BDA0005277514850000081
Patent Text Reader

Abstract

The application belongs to the field of plastic materials, and specifically discloses a flame-retardant PC / ABS composition, a preparation method and application thereof.The flame-retardant PC / ABS composition comprises the following components in parts by weight: PC 39-61 parts, ABS 2.5-11 parts, mica powder 34-46 parts, glass fiber 1.5-8.5 parts, flame retardant 4.5-11 parts, and anti-dripping agent 0.1-2.1 parts; the mica powder comprises mica powder A and mica powder B, the mesh number of the mica powder A is 300-600 mesh, and the mesh number of the mica powder B is 20-40 mesh.The 300-600 mesh mica powder A and the 20-40 mesh mica powder B are compounded, the two kinds of mica powder can complement each other, the rigidity of the composition can be effectively improved, the linear expansion coefficient and anisotropy can be effectively reduced, and the flame-retardant PC / ABS composition with high rigidity and dimensional stability is comprehensively realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of plastics, specifically relating to a flame-retardant PC / ABS composition, its preparation method, and its application. Background Technology

[0002] Flame-retardant PC / ABS is a commonly used plastic alloy with excellent mechanical properties, flame retardancy, weather resistance, and heat resistance, and is widely used in the automotive, office, and home appliance industries. With the increasing demand for thinner and lighter materials in various industries, the performance requirements for traditional flame-retardant PC / ABS alloys are also becoming more stringent. For example, there is a need to improve the rigidity and dimensional stability of the material. Therefore, developing flame-retardant PC / ABS alloys with high rigidity and good dimensional stability is of great significance.

[0003] Dimensional stability refers to a material's ability to maintain its original dimensions under different environmental conditions. The coefficient of linear expansion (CLTE) is a crucial characteristic characterizing a material's dimensional stability; it is the ratio of the change in length (ΔL) to the initial length (L) over a unit temperature change (ΔT), i.e., CLTE = ΔL / (L × ΔT). Anisotropy of the CLTE refers to the difference in the CLTE across different directions of the material, typically characterized by the difference in CLTE between the flow direction (MD) and perpendicular to the flow direction (TD). The CLTE and its anisotropy directly affect the dimensional stability of a material. If a material's CLTE is too large, or if the differences in CLTE across different directions are significant, then upon temperature changes, its various parts may expand or contract at different rates, leading to uneven changes in overall dimensions. This unevenness can cause the material to bend, twist, or warp, thereby reducing dimensional stability.

[0004] Adding inorganic fillers such as glass fiber, talc, wollastonite, barium sulfate, magnesium sulfate whiskers, and nano-silica can suppress the mobility of molecular chains, thereby reducing the linear expansion coefficient of amorphous polymers and improving the material's rigidity to some extent. Glass fiber significantly improves rigidity; however, as an anisotropic inorganic filler, it is particularly prone to orientation effects, leading to increased anisotropy in the linear expansion coefficient and making dimensional stability difficult to achieve. Meanwhile, fillers such as talc, wollastonite, barium sulfate, magnesium sulfate whiskers, and nano-silica do not significantly improve rigidity and cannot meet practical requirements for high rigidity. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of existing flame-retardant PC / ABS materials, such as large linear expansion coefficient, high anisotropy, and insufficient rigidity. This invention will provide a flame-retardant PC / ABS composition, its preparation method, and its application.

[0006] To achieve the above objectives, the following technical solutions are specifically included:

[0007] On one hand, the present invention provides a flame-retardant PC / ABS composition comprising the following components in parts by weight:

[0008] PC 39-61 parts, ABS 2.5-11 parts, mica powder 34-46 parts, glass fiber 1.5-8.5 parts, flame retardant 4.5-11 parts, anti-dripping agent 0.1-2.1 parts; the mica powder includes mica powder A and mica powder B, wherein the mesh size of mica powder A is 300-600 mesh and the mesh size of mica powder B is 20-40 mesh.

[0009] Mica powder is a layered filler. When the average particle size of mica sheets is small (i.e., larger mesh size), it can better maintain its original layered morphology during material processing, giving the material good rigidity. However, it is prone to orientation along the processing flow direction with the resin matrix, resulting in greater CLTE anisotropy in the material. When the average particle size of mica sheets is large (i.e., smaller mesh size), sheet dissociation and wrinkling are more likely to occur during processing, weakening its orientation effect along the flow direction, thus giving the material a lower linear expansion coefficient anisotropy. However, its effect on improving material rigidity is poor. In addition, its effective migration to the combustion surface during combustion decreases, and it is also prone to deteriorating flame retardant properties. Through repeated research, the inventors of this invention discovered that by compounding 300-600 mesh mica powder A and 20-40 mesh mica powder B, the two mica powders can complement each other, not only effectively improving the rigidity of the composition but also effectively reducing the linear expansion coefficient and its anisotropy. Furthermore, the flame retardant properties of the composition can reach UL94 for 1.5mm samples. V1 and above are flame-retardant PC / ABS compositions that combine high rigidity, low linear expansion coefficient, and anisotropy.

[0010] Preferably, the flame-retardant PC / ABS composition comprises the following components in parts by weight: 40-60 parts PC, 3-10 parts ABS, 35-45 parts mica powder, 2-8 parts glass fiber, 5-10 parts flame retardant, 0.2-2 parts anti-dripping agent, and 0-3 parts processing aid.

[0011] Preferably, in the flame-retardant PC / ABS composition, the mass percentage of PC (polycarbonate) is not less than 30%, more preferably not less than 40%, and even more preferably not less than 45%.

[0012] The system of this invention does not limit the type of PC. The polycarbonate is preferably bisphenol A type polycarbonate, but self-made PC can also be used. For example, the melt flow rate of the polycarbonate can be 1-60 g / 10 min, wherein the melt flow rate is tested according to ISO 1133-1 2011 standard, and the test conditions are 300℃ and 1.2 kg. More specifically, the melt flow rate of the polycarbonate can be 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60 g / 10 min, etc., as well as specific point values ​​between the above points. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific point values ​​included in the range.

[0013] Preferably, the ABS is a terpolymer of acrylonitrile, butadiene, and styrene. The system of the present invention does not limit the type of ABS. Commercially available conventional ABS or self-made ABS can be used. For example, ABS with a melt flow rate of 1-30 g / 10 min tested at 220 °C and 10 kg according to GB / T3682-2000 can be used. More specifically, the melt flow rate of ABS can be 1, 3, 9, 12, 15, 18, 21, 24, 27, 30 g / 10 min, etc., as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0014] In the system of the present invention, the mesh size of mica powder A is 300-600 mesh, and more preferably the mesh size of mica powder A is 400-500 mesh. Specifically, it can be 300, 325, 350, 375, 400, 425, 450, 475, 500, 525, 550, 575, 600 mesh, etc., as well as specific mesh values ​​between the above mesh values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific mesh values ​​included in the range.

[0015] Preferably, the iron oxide content in mica powder A and mica powder B is 0.5-5% by mass, specifically 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, etc., as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range.

[0016] Preferably, the mica powder A further comprises the following components in weight percentage: SiO2 40%-45%, Al2O3 10%-14%, K2O 9%-12%, Na2O 0.3%-0.5%, MgO 30%-33%, CaO 0.1%-0.5%, and TiO2 0.1%-0.5%.

[0017] More preferably, the mica powder A further comprises the following components in weight percentage: SiO2 40.5%-42%, Al2O3 11%-13%, K2O 11%-11.5%, Na2O 0.35%-0.4%, MgO 32%-33%, CaO 0.2%-0.3%, and TiO2 0.2%-0.25%.

[0018] Preferably, the mica powder B further comprises the following components in weight percentage: SiO2 50%-52%, Al2O3 30%-32%, K2O 9%-11%, Na2O 0.3%-0.5%, MgO 0.5%-1%, CaO 0.8%-1%, and TiO2 0.8%-1%.

[0019] The inventors of this invention discovered that when the iron oxide mass percentage in mica powder is 0.5-5%, the material exhibits a low coefficient of linear expansion. When the iron oxide mass percentage in mica powder A and mica powder B is below 0.5%, the coefficient of linear expansion and its anisotropy increase; when the iron oxide mass percentage in mica powder A and mica powder B is above 5%, the flame retardant performance deteriorates. The mesh size and iron oxide content of the mica powder are measured using conventional methods. In this invention, the mesh size of the mica powder is measured by a grid sieving method, and the iron oxide content can be obtained by inductively coupled plasma mass spectrometry (ICP-MS).

[0020] Preferably, the mass ratio of mica powder A to mica powder B is 1:(0.3-3), more preferably 1:(0.5-1), and specifically can be 1:0.3, 1:0.5, 1:0.7, 1:0.9, 1:1.1, 1:1.3, 1:1.5, 1:1.7, 1:1.9, 1:2.1, 1:2.4, 1:2.6, 1:2.8, 1:3, etc., as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific values ​​included in the range.

[0021] Preferably, the glass fiber is a conventional round glass fiber or a flat glass fiber, and the average diameter of the glass fiber is 10-17 μm, specifically 10, 11, 12, 13, 14, 15, 16, 17 μm, etc., as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0022] Preferably, the average length of the glass fiber is 3-4.5 mm.

[0023] Preferably, the flame retardant is a phosphorus-based flame retardant, and more preferably, the flame retardant includes at least one of bisphenol A diphenyl phosphate, resorcinol diphenyl phosphate, triphenyl phosphate, and 4,4'-(isopropylidene diphenyl)bis(diphenyl phosphate).

[0024] Preferably, the anti-dripping agent comprises polytetrafluoroethylene.

[0025] Preferably, the flame-retardant PC / ABS composition further includes 0.1-3.5 parts by weight of processing aids.

[0026] Preferably, the processing aid comprises the following components in parts by weight: 0.1-1 parts antioxidant and 0.1-1 parts lubricant.

[0027] More preferably, the antioxidant is a hindered phenolic antioxidant.

[0028] On the other hand, the present invention provides a method for preparing the flame-retardant PC / ABS composition, comprising the following steps:

[0029] The raw materials are sequentially mixed, melted, extruded, and granulated to obtain the flame-retardant PC / ABS composition.

[0030] Preferably, the melting temperature is 210–250°C.

[0031] Preferably, the rotation speed during melting is 200 to 600 revolutions per minute.

[0032] The present invention also provides an application of the flame-retardant PC / ABS composition described above in the preparation of automotive parts, office supplies, and household appliances, specifically in the preparation of laptop casings and television casings.

[0033] Compared with the prior art, the present invention has the following beneficial effects: By compounding 300-600 mesh mica powder A and 20-40 mesh mica powder B, the two mica powders can complement each other's strengths and weaknesses. While maintaining good flame retardant properties, the rigidity of the composition can be effectively improved, and the linear expansion coefficient and its anisotropy can be effectively reduced, thus achieving a flame retardant PC / ABS composition with high rigidity and dimensional stability. Detailed Implementation

[0034] To better illustrate the purpose, technical solution, and advantages of this invention, specific embodiments will be used to further explain the invention below. Unless otherwise specified, the experimental methods used in the embodiments and / or comparative examples are conventional methods; the materials and reagents used, unless otherwise specified, are commercially available. Unless otherwise specified, the raw materials used in each embodiment and comparative example of this invention are the same in each parallel experiment.

[0035] Raw material information involved in the following examples and comparative examples:

[0036] PC resin: PC 1300 10NP, LG Chem Ltd., South Korea;

[0037] ABS resin: 275, Shanghai Gaoqiao;

[0038] Mica powder A1: after sieving to 300 mesh, SiO2: 42wt.%, Al2O3: 13wt.%, K2O: 11wt.%, Na2O: 0.4wt.%, MgO: 32.7wt.%, CaO: 0.2wt.%, TiO2: 0.2wt.%, Fe2O3: 0.5wt.%, Huajing mica;

[0039] Mica powder A2: 400 mesh, Fe2O3 content is 0.5 wt.%, obtained by grinding and sieving mica powder A1;

[0040] Mica powder A3: 500 mesh, Fe2O3 content is 0.5 wt.%, obtained by grinding and sieving mica powder A1;

[0041] Mica powder A4: 600 mesh, Fe2O3 content is 0.5 wt.%, obtained by grinding and sieving mica powder A1;

[0042] Mica powder A5: 800 mesh, Fe2O3 content is 0.5 wt.%, obtained by grinding and sieving mica powder A1;

[0043] Mica powder A6: 400 mesh, SiO2: 40.5 wt.%, Al2O3: 11.1 wt.%, K2O: 11.5 wt.%, Na2O: 0.35 wt.%, MgO: 33 wt.%, CaO: 0.3 wt.%, TiO2: 0.25 wt.%, Fe2O3: 3 wt.%, Huajing mica;

[0044] Mica powder A7: 400 mesh, SiO2: 43wt.%, Al2O3: 10.6wt.%, K2O: 10wt.%, Na2O: 0.5wt.%, MgO: 30wt.%, CaO: 0.5wt.%, TiO2: 0.4wt.%, Fe2O3: 5wt.%, Huajing mica;

[0045] Mica powder B1: after sieving to 20 mesh, SiO2: 51wt.%, Al2O3: 31wt.%, K2O: 10wt.%, Na2O: 0.4wt.%, MgO: 0.8wt.%, CaO: 0.9wt.%, TiO2: 0.9wt.%, Fe2O3: 5wt.%, Huajing mica;

[0046] Mica powder B2: 30 mesh, Fe2O3 content is 5wt.%, obtained by grinding and sieving mica powder B1;

[0047] Mica powder B3: 40 mesh, Fe2O3 content is 5wt.%, obtained by grinding and sieving mica powder B1;

[0048] Mica powder B4: 60 mesh, Fe2O3 content is 5wt.%, obtained by grinding and sieving mica powder B1;

[0049] Fiberglass 1: ECS13-4.5-534A, average diameter 13μm, chopped into 4.5mm lengths, China Jushi Co., Ltd.;

[0050] Fiberglass 2: ECS10-4.5-568H, average diameter 10μm, short cut into 3mm pieces, China Jushi Co., Ltd.;

[0051] Fiberglass 3: EDR17-2400-988A, average diameter 17μm, chopped into 4.5mm lengths, China Jushi Co., Ltd.;

[0052] Phosphorus-based flame retardant: BDP (Bisphenol A-bis(diphenyl phosphate)), Wansheng;

[0053] Anti-dripping agent: Polytetrafluoroethylene, commercially available;

[0054] Processing aids: Antioxidant 1010, commercially available.

[0055] Examples 1-16 and Comparative Examples 1-4

[0056] A method for preparing a flame-retardant PC / ABS composition includes the following steps:

[0057] (1) According to the amount of raw material components in Table 1-2, stir and mix each component in a high-speed mixer to obtain a premix;

[0058] (2) The premixed material is fed into a twin-screw extruder through the main feed port, melt-mixed and extruded and granulated in the twin-screw extruder to obtain the flame-retardant PC / ABS composition, wherein the screw length-to-diameter ratio is 45:1, the screw barrel temperature is 210-250℃, and the screw speed is 300rpm.

[0059] The test methods for various properties of the flame-retardant PC / ABS compositions of the present invention in the embodiments and comparative examples are as follows:

[0060] (1) Bending modulus test: conducted according to ASTM D790-2010, with a bending rate of 2 mm / min; bending modulus > 9000 MPa is considered qualified;

[0061] (2) Flame retardancy rating: Flame retardancy testing was conducted according to the "Flammability Testing of Plastic Materials, UL94-2019" standard. The flame retardancy rating was determined based on the burning rate, extinguishing time, resistance to dripping, and whether the dripping material was actively burning. The sample used for testing was 125mm long and 13mm wide. In this invention, the thickness was selected as 1.5mm during testing. According to the UL94-2019 standard, the flame retardancy rating of materials can be classified as UL94 V0, V1, V2, etc.; a flame retardancy rating of V-1 or higher is considered qualified.

[0062] (3) Linear expansion coefficient test: The test shall be conducted in accordance with ISO 11359-2-1999, where the flow direction (MD) is the direction of glue injection and the perpendicular flow direction (TD) is the direction perpendicular to glue injection; the difference between the two directions, CLTE-TD / MD, is ≤25μm / (m.℃) and is considered to be qualified.

[0063] The test results are shown in Table 3.

[0064] Table 1 (parts by weight)

[0065]

[0066] Table 2 (parts by weight)

[0067]

[0068]

[0069] Table 3

[0070]

[0071] As can be seen from the above embodiments, the flame-retardant PC / ABS composition of the present invention has a flexural modulus > 9000MPa, a flame retardant rating of V-1 or higher, and a CLTE-TD / MD difference ≤ 25μm / (m.℃), exhibiting excellent rigidity, flame retardant properties, and dimensional stability.

[0072] As can be seen from Example 1 and Comparative Examples 1 and 3, when mica powder A is used alone, the flexural modulus is high, but the difference between the CLTE values ​​in the MD and TD directions increases significantly, and the linear expansion coefficient and its anisotropy are relatively high; when mica powder B is used alone, the flexural modulus decreases significantly and the flame retardant performance is poor; only by using a combination of mica powder A and mica powder B can the PC / ABS composition obtain good rigidity, flame retardant performance and a low linear expansion coefficient and its anisotropy. Meanwhile, in Comparative Example 2 (Examples 2, 1, 3, and 4), the mesh size of mica powder A gradually increased, the particle size of mica powder gradually decreased, and the differences in flexural modulus, flame retardant properties, and CLTE values ​​in the MD and TD directions gradually increased. In Comparative Example 4 (Examples 5, 1, and 6), the mesh size of mica powder B gradually increased, the particle size of mica powder gradually decreased, and the differences in flexural modulus, flame retardant properties, and CLTE values ​​in the MD and TD directions gradually increased. Among them, the mesh size of mica powder A in Comparative Example 2 exceeded 600 mesh, and the mesh size of mica powder B in Comparative Example 4 exceeded 40 mesh. At this time, the particle size compatibility of mica powder A and mica powder B was poor, resulting in poor flame retardant properties of the PC / ABS composition and high linear expansion coefficient and anisotropy, making the product obviously unqualified. Therefore, it can be seen that only when the mesh size of mica powder A is 300-600 mesh and the mesh size of mica powder B is 20-40 mesh can the two mica powders effectively complement and cooperate with each other, thus achieving excellent rigidity, flame retardant properties and dimensional stability.

[0073] In Examples 7, 8, 1, 9, and 10, the mass ratios of mica powder A to mica powder B were 1:0.3, 1:0.5, 1:0.75, 1:1, and 1:3, respectively. The differences in flexural modulus, flame retardancy, and CLTE values ​​in the MD and TD directions gradually decreased. It is evident that the mass ratio of mica powder A to mica powder B has a certain impact on rigidity, flame retardancy, and dimensional stability. Within a mass ratio of 1:(0.3-3), the rigidity, flame retardancy, and dimensional stability of the PC / ABS composition are satisfactory. Further optimization is achieved when the mass ratio of mica powder A to mica powder B is 1:(0.5-1), at which point the rigidity, flame retardancy, and dimensional stability of the PC / ABS composition are even better.

[0074] In Examples 11, 1, and 12, the average diameters of the glass fibers were 10 μm, 13 μm, and 17 μm, respectively. As the average diameter of the glass fibers increased, the flexural modulus gradually increased. However, the difference between the CLTE in the MD and TD directions first decreased and then increased. It can be seen that in the system of the present invention, selecting an average glass fiber diameter of 10-17 μm can balance good rigidity and dimensional stability.

[0075] In Examples 1, 15, and 16, the iron oxide content of mica powder A was 0.5 wt.%, 3 wt.%, and 5 wt.%, respectively. The materials had similar rigidity. As the iron oxide content increased, the difference between MD and TD directions CLTE decreased. When the iron oxide content was between 0.5 and 5 wt.%, the material could obtain better dimensional stability.

[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A flame-retardant PC / ABS composition, characterized in that, The components include the following parts by weight: PC 39-61 parts, ABS 2.5-11 parts, mica powder 34-46 parts, glass fiber 1.5-8.5 parts, flame retardant 4.5-11 parts, anti-dripping agent 0.1-2.1 parts; The mica powder includes mica powder A and mica powder B, wherein the mesh size of mica powder A is 300-600 mesh and the mesh size of mica powder B is 20-40 mesh; the mass ratio of mica powder A to mica powder B is 1:(0.3-3).

2. The flame-retardant PC / ABS composition as described in claim 1, characterized in that, The mica powder A has a mesh size of 400-500.

3. The flame-retardant PC / ABS composition as described in claim 1, characterized in that, The mica powder B has a mesh size of 30-35.

4. The flame-retardant PC / ABS composition as described in claim 1, characterized in that, The average diameter of the glass fiber is 10-17 μm.

5. The flame-retardant PC / ABS composition as described in claim 1, characterized in that, The flame retardant includes at least one of bisphenol A diphenyl phosphate, resorcinol diphenyl phosphate, triphenyl phosphate, and 4,4'-(isopropylidene diphenyl)bis(diphenyl phosphate).

6. The flame-retardant PC / ABS composition as described in claim 1, characterized in that, Includes at least one of the following: The anti-dripping agent includes polytetrafluoroethylene; The iron oxide content in mica powder A and mica powder B is 0.5-5% by mass.

7. The flame-retardant PC / ABS composition as described in claim 1, characterized in that, It also includes 0.1-3.5 parts by weight of processing aids, which include the following components in parts by weight: 0.1-1 parts of antioxidant and 0.1-1 parts of lubricant.

8. A method for preparing the flame-retardant PC / ABS composition according to any one of claims 1-7, characterized in that, The process includes the following steps: mixing, melting, extruding, and granulating the raw materials in sequence to obtain the flame-retardant PC / ABS composition.

9. The use of the flame-retardant PC / ABS composition according to any one of claims 1-7 in the preparation of automotive parts, office supplies, and household appliances.

Citation Information

Patent Citations

  • Polypropylene composite material with low linear expansion coefficient and preparation method and application thereof

    CN106147034A

  • A high-flame-retardant high-rigidity PC / ABS material and a product thereof

    CN109867935A